Bioidentical hormone therapy: An assessment of provider knowledge. (December 2016) - Files, Julia A.; Kransdorf, Lisa N.; Ko, Marcia; Kling, Juliana M.; David, Paru S.; Pruthi, Sandhya; Sood, Richa; Creedon, Douglas; Chang, Yu-Hui H.; Mayer, Anita P.
Highlights: Custom-compounded bioidentical hormone therapy has become very popular, despite the lack of scientific data supporting its use. In a survey, less than half of the healthcare providers who prescribed custom-compounded bioidentical hormone therapy actually felt comfortable doing so. Opportunity exists to educate providers regarding bioidentical hormone therapy. Abstract: Objectives: Bioidentical hormone therapy (BHT) is available in the United States in formulations that have been approved by the Food and Drug Administration (FDA) but also in formulations that have not been so approved. The aim of this study was to evaluate the knowledge, beliefs, and prescribing practices of BHT among healthcare providers. Study design: A cross-sectional self-selected responder survey was conducted of health care providers attending primary care Continuing Medical Education (CME) conferences in the United States from May 2012 to April 2013. The questionnaire consisted of 26 items assessing knowledge, beliefs, and current practice around BHT. Results: A total of 366 survey responses were analyzed. Though 69.8% of respondents accurately identified the definition of BHT, only 45.3% were aware that BHT is available in FDA-approved products and 34.2% of respondents incorrectly identified that BHT is available only in custom-compounded formulations. Of those who had prescribed CC-BHT, less than half agreed with the statement "I am comfortable prescribing BHT" (45.4%). Conclusions: Our study showed that many practitioners are unaware that bioidentical hormones are available in FDA-approved products. Knowledge gaps identified by this survey highlight the need for and importance of education to further dispel misinformation surrounding the topic.